TUNGGAL HATI SEMINARI-TUNGGAL HATI MARIA (THS-THM) DALAM PEMBINAAN DAN PEMBENTUKAN IMAN, MENTAL, DAN FISIK KAUM MUDA KATOLIK KOTA KUPANG - Yudabbirul Arif; Ronald Dwi. Ardian Fufu; Yohanes Dominggo (Nusa Cendana University, 2022)
This research aims to find out how the process of fostering THS-THM in the formation of the faith, mental, and physical of young Catholics and information for the whole community especially Catholics about THS-THM itself. The study was conducted for 1 month and was located in four Catholic Churches namely St. Peter's Parish Rasul TDM, Christ King Kupang Parish, Sta Parish. Maria Assumpta and The Parish of St. Francis Assisi BTN located in the territory of the Archdiocese of Kupang, East Nusa Tenggara. The methods carried out in this study are qualitative desriptive research with data collection through observation in the field, interviews to members of the pencak silat organization THS-THM, and documentation from the pencak silat organization THS-THM. Data / information obtained from sources, namely the builder / companion / twig advisor, and the chairman / coordinator of the pencak silat organization THS-THM. In this study explained about the process of fostering THS-THM in shaping faith, mental, and physical for its members and for young Catholics who joined the THS-THM Organization. The results showed that the Pencak Silat Organization THS-THM is a forum for fostering in the formation of the faith, mental, and physical of young Catholics. Pencak Silat THS-THM is a Church organization under the auspices of the Indonesian Catholic Church whose job is to help launch pastoral ministry activities in serving the Church and society. Factors that often hamper the process of fostering THS-THM organizations in the formation of faith, mental, and physical Catholic youth are the health of candidates and members disturbed (sick), busy work and education, the challenges of the times, and the influence of technology and the environment. The coaching process carried out by the THS-THM organization has a positive impact on its members.